2017
DOI: 10.1016/j.immuni.2017.03.018
|View full text |Cite
|
Sign up to set email alerts
|

An Amphibian Host Defense Peptide Is Virucidal for Human H1 Hemagglutinin-Bearing Influenza Viruses

Abstract: Although vaccines confer protection against influenza A viruses, antiviral treatment becomes the first line of defense during pandemics because there is insufficient time to produce vaccines. Current antiviral drugs are susceptible to drug resistance, and developing new antivirals is essential. We studied host defense peptides from the skin of the South Indian frog and demonstrated that one of these, which we named "urumin," is virucidal for H1 hemagglutinin-bearing human influenza A viruses. This peptide spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 43 publications
1
67
0
4
Order By: Relevance
“…In the in vivo assays, BALB/C mice were treated with urumin, administered intranasally, and then inoculated with influenza. The results showed that urumin-treated mice had less morbidity than the non-treated [95].…”
Section: Avps Derived From Amphibiansmentioning
confidence: 95%
“…In the in vivo assays, BALB/C mice were treated with urumin, administered intranasally, and then inoculated with influenza. The results showed that urumin-treated mice had less morbidity than the non-treated [95].…”
Section: Avps Derived From Amphibiansmentioning
confidence: 95%
“…Peptide‐based medicines include Lupron, which achieved global sales of more than US$2.3 billion in 2011, antimicrobial peptides, and GLP‐1 agonists which represent an established drug class with several products currently available in the market including Byetta, Bydureon, Victoza, Lyxumia, and Tanzeum which are used in the treatment of Type‐2 diabetes and obesity (Fosgerau & Hoffmann, ). In addition, researchers from Emory Vaccine Centre and the Rajiv Gandhi Centre for Biotechnology in India have recently reported that a peptide found in the skin mucus secreted by South Indian frogs is virucidal for H1 hemagglutinin‐bearing human influenza A viruses (Holthausen et al, ). This peptide, named Urumin is a unique class and shows potential to contribute to first‐line antiviral treatments during influenza outbreaks.…”
Section: Present and Future Of Bioactive Peptidesmentioning
confidence: 99%
“…Bioactive peptides are currently used by pharmaceutical companies for health promotion. It has been estimated that the global peptide drug market will increase from US$14.1 billion in 2011 to US$25.4 billion in 2018 (Fosgerau & Hoffmann, 2015 (Holthausen et al, 2017). This peptide, named Urumin is a unique class and shows potential to contribute to first-line antiviral treatments during influenza outbreaks.…”
Section: Pr E S En T a N D Fu T Ur E O F Bi O A Cti V E Pe P Ti D Esmentioning
confidence: 99%
“…Over the next several months, Jacob isolated 32 different peptides from the H. bahuvistara slime, all of which were new to science, including one that seemed able to thwart the H1N1 flu virus in both cells in a dish and mice. Jacob's team named this compound urumin, after the long, curved sword historically carried by soldiers in the same region of southern India where the frog lived 1 .…”
Section: By Carrie Arnoldmentioning
confidence: 99%